Development and application of a new statistical analysis for deriving horizontal phase velocity distribution of gravity waves from airglow imaging at Syowa Station (69S, 39E), Antarctica - T, Matsuda; T.Nakamura; M.K.Ejiri; T, Tsutsumi; K, Shiokawa; Y, Tomikawa (2013)
第4回極域科学シンポジウム 横断セッション：[IM] 中層大気・熱圏 11月14日（木）〜15日（金） 国立極地研究所 2階大会議室前ラウンジ conference object